2020
DOI: 10.3892/etm.2020.9092
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microRNA‑186 and vascular endothelial growth factor in hepatocellular carcinoma complicated with portal vein tumor thrombus

Abstract: The present study aims to investigate the role and underlying mechanism of microRNA (miR)-186 in patients with hepatocellular carcinoma (HCC) complicated with portal vein tumor thrombus. Blood samples from 29 HCC patients with portal vein tumor thrombus were collected between January 2014 and September 2015 in Huai'an First People's Hospital, while blood from 36 HCC patients without vein tumor thrombus was also collected in the same period. In addition, tumor thrombus specimens were collected from the HCC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In pathology, a vascular tumor thrombus is used as an important biological indicator to evaluate the degree of malignancy and is an important marker of recurrence and prognosis. Moreover, studies have confirmed that it is also a risk factor for lymph node metastasis ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 95%
“…In pathology, a vascular tumor thrombus is used as an important biological indicator to evaluate the degree of malignancy and is an important marker of recurrence and prognosis. Moreover, studies have confirmed that it is also a risk factor for lymph node metastasis ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 95%
“…However, the mechanism of tumor thrombosis induced by malignant tumors is still unclear. (Yuan and Li 2020) Aberrant expression levels of MicroRNAs (miRNAs) have been detected in various human malignancies, which closely correlated with cell proliferation, differentiation, migration, invasion and apoptosis (Jiang et al 2022). It is generally considered that PVTT is a special type of metastasis of HCC (Wang et al 2019; Elhendawy et al 2020).…”
Section: Introductionmentioning
confidence: 99%